Analysis of Accounting Information Systems of Cash Receipts and Cash Dispenses at PT. JNE Medan Main Branch - Sylviana Siregar; Nurwani Nurwani; Hendra Harmain (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study aims to find out how the accounting information system procedures for the application of cash and cash disbursements at PT. JNE Medan Main Branch in 2023. The research method uses a qualitative descriptive method which includes field studies. The data used in this study are primary data and secondary data. Data collected by means of observation, interviews and documentation. Based on the analysis and discussion above, it can be concluded that cash receipts and cash disbursements at PT. JNE Medan Main Branch has implemented an accounting information system well using two ways, namely the first is to manually write down all transactions that occur, both cash receipts and cash disbursements. Second, digitally assisted by the Microsoft Office Excel and MDAX software systems which are already connected to the center of PT. JNE with PT. JNE spread across Indonesia. The procedure for cash receipts in the accounting department by this company still does not record transactions in general journals and posting ledgers, but PT. JNE Medan Main Branch already uses MDAX which helps record and report company finances in real time at the company center.